2021
DOI: 10.1155/2021/6677687
|View full text |Cite
|
Sign up to set email alerts
|

The Cyr61 Is a Potential Target for Rotundifuran, a Natural Labdane‐Type Diterpene from Vitex trifolia L., to Trigger Apoptosis of Cervical Cancer Cells

Abstract: Cervical cancer is a common female malignant tumor that seriously threatens human health. This study explored the anticervical cancer effects and potential mechanisms of Rotundifuran (RTF), a natural product isolated from Vitex trifolia L. In this study, we found that RTF can suppress the proliferation of cervical cancer cell lines, including HeLa and SiHa cells (with the IC50 less than 10 μM), via induction of apoptosis in vitro, and the antitumor effect of RTF is further confirmed on the HeLa cell-inoculated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…The present study showed that CF treatment significantly decreased LDH and CK in H 2 O 2 -treated H9c2 cells. Cell cycle arrest has been reported to be closely related to apoptosis induction, and our present study found that CFE protected H9c2 cells from cell cycle arrest caused by H 2 O 2 [ 30 ].…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…The present study showed that CF treatment significantly decreased LDH and CK in H 2 O 2 -treated H9c2 cells. Cell cycle arrest has been reported to be closely related to apoptosis induction, and our present study found that CFE protected H9c2 cells from cell cycle arrest caused by H 2 O 2 [ 30 ].…”
Section: Discussionmentioning
confidence: 63%
“…Combined with the results of PPI and essential genes analysis of CFE against MI, we think the anti-apoptosis and anti-oxidative stress via Akt/Nrf2 signaling is the main potential molecular mechanisms of CF. In addition, ROS are an important index reflecting oxidative stress in cells, and overproduction of ROS can induce apoptosis in cells [ 30 , 31 ]. Interestingly, our results showed that CFE reduced the ROS levels in H9c2 cells induced by H 2 O 2 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PI3K/Akt pathway is an important cellular pathway occupying a pivotal role in the mediation of cell apoptosis[ 34 ]. A recent study demonstrated that Rotundifuran-induced ROS production could lead to cell apoptosis via suppressing the PI3K/Akt pathway in the cervical cancer cell model[ 35 ]. Another study also showed that inhibition of apoptosis was correlated with the ROS-mediated PI3K/Akt pathway in a streptozotocin-treated INS-1 cell model[ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…2'-Hydroxycinnamaldehyde, a natural product isolated from the stem bark of Cinnamomum cassia, was found to selectively inhibit STAT3 activity by directly binding to STAT3 using a pull-down assay, DARTS and CETSA experiments 51 . Using proteomics analysis and DARTS methods, cysteine-rich angiogenic inducer 61 (Cyr61) was identified as a potential target for rotundifuran, a natural product isolated from Vitex trifolia L , in cervical cancer cells 101 . In the process of screening NAPs that inhibit STAT3 using DARTS and CETSA methods, geranylnaringenin was found to reduce luciferase activity in a dose-dependent manner and then regulate STAT3 activity by interacting with SHP-2 54 .…”
Section: Direct Screening Strategies Based On the Differential Limite...mentioning
confidence: 99%